Pengaruh Voucher Tiktok dan Inovasi Produk terhadap Keputusan Pembelian Roti’O - Siska Setyani; Anes Arini; Anna Probowati (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
The researcher will examine the influence of TikTok vouchers and product innovation on purchasing decisions for Roti’O, employing a quantitative survey model. Population of 100 Roti’O consumers in Purworejo Regency who had made purchases using TikTok vouchers, selected via purposive sampling. Report analysis was conducted using SPSS version 26, covering reliability, validity, the coefficient of determination, multiple linear regression, the F-test, and the t-test. The results regarding the impact of TikTok vouchers on purchasing decisions showed a t-statistic greater than the t-table value (2.532 > 1.984) with a significance level of 0.013 < 0.05; thus, H1—asserting that TikTok vouchers make a significant positive contribution to purchasing decisions—was accepted, and H0 was rejected. Similarly, the analysis of product innovation’s impact on purchasing decisions yielded a t-statistic greater than the t-table value (5.526 > 1.984) with a significance level of 0.000 < 0.05; consequently, H2—asserting that product innovation makes a significant positive contribution to purchasing decisions—was accepted, and H0 was rejected. These findings indicate that both variables play a crucial role in enhancing consumer purchasing decisions regarding Roti’O products in Purworejo Regency.